Salvage therapy with Sodium chlorosum (formerly DAC N-055) for cases of refractory lupoid cutaneous leishmaniasis: Results from a compassionate use study with 0.09% Sodium chlorosum in amphiphilic basic cream - Molkara, Sara; Poursoltani, Elaheh; Stahl, Kurt Wilhelm; Maleki, Masoud; Khamesipour, Ali; Bogdan, Christian; Salehi, Maryam; Goyonlo, Vahid Mashayekhi (BMC Infectious Diseases, 2019)
Background: Lupoid cutaneous leishmaniasis (LCL) is known as a rare but serious complication of anthroponotic cutaneous leishmaniasis (ACL) resistant to conventional treatments. Sodium chlorosum, a pro-oxidative preparation of pharmaceutical sodium chlorite (NaClO2), has been successfully used for the treatment of Old World cutaneous leishmaniasis lesions (OWCL) and of some LCL cases in Afghanistan. This clinical trial study aimed to evaluate the effect of a last resort therapy with topical 0.09% sodium chlorosum on LCL in Iran. Methods: Twenty Iranian patients (12 women and 8 men) with LCL refractory to treatment were included in this salvage study. A magistral preparation of sodium chlorosum (10 mM NaClO2 in amphiphilic basic cream) was applied twice daily to the lesions for 6 weeks and continued up to 12 weeks in patients who showed a clinical response within the first 6 weeks. Responders were followed up for a maximum of 1 year. Lesions were photographed during weekly visits. Disappearance of erythema and indurated lesions were rated as complete clinical response. Results: Patients with a mean age of 28.6 (±24.3) and with an ACL proven lesion history of 3.8 (±1.4) years were treated for an average of 7.9 (±1.8) weeks. At the end of the treatment period (12th week), a complete response was observed in 9 of 20 patients (45%). During the one-year follow-up period, LCL lesions recurred in 4 of these 9 patients (with one patient showing only a tiny lesion) and one case lost to follow up whereas the other four remained completely lesion-free. Mild temporary side-effects such as erythema and itching were seen in 4 of 20 patients (20%). Conclusions: Topical sodium chlorosum showed promising therapeutic results and can be considered as safe, painless, and relatively effective treatment for LCL, an ethical prerequisite for a two-armed controlled trial. Trial registration: This study was registered in Iranian registry of clinical trials on 2019-02-02 with registration number IRCT20190114042356N1.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Lupoid cutaneous leishmaniasis; Sodium chlorosum (formerly DAC N-055); Treatment